Social and Health Factors Associated with Physical Activity among Kuwaiti College Students - Abdulwahab Naser Al-Isa; Jennifer Campbell; Ediriweera Desapriya; Namal Wijesinghe (Hindawi Limited, 2011)
Our aim was to explore the social and health factors that are associated with the level of physical activity among Kuwaiti college students. A random sample of 787 students (48% males and 52% females) was chosen and weight and height were measured to obtain body mass index (BMI, kg/m2). Associated social and health factors were obtained using a questionnaire. Those reporting being physically inactive numbered 354 and the remaining 433 were active. Obesity among males was 13% and was 10.5% among females. The social and health factors that were found to be significantly associated with physical activity among the students were gender (P<.001), marital status (P<.05), BMI category (obese or nonobese) (P<.05), last dental and health checkup (P<.01), desiring a higher degree (P<.001), and countries preferred for visiting (P<.01). Males significantly exceeded females in the practice of physical activity. In conclusion, behavioural modifications, intervention studies, and health education touting the benefits of being physically active should be instituted to increase the practice of sports and other physical activities in order to control and decrease obesity-related morbidity and mortality.